Studi Biblika Tentang Perceraian Berdasarkan Kitab Perjanjian Baru - Isunmiati Sidin (Sekolah Tinggi Teologi Bethel Ambon, 2020)
The purpose of this research is to get a deep understanding of the principle of divorce in the book of the Blind Agreement. Researchers use the exegesis research method which is a careful and analytical study of a part of the Bible in order to achieve useful interpretations. Divorce is not God's plan, because